Solving Stock Price-Gross Domestic Product Puzzle: Evidence from Sri Lanka - Jahfer, Athambawa; Inoue, Tohru (International Journal of Economics and Financial Issues, 2017)
This paper investigates the macroeconomic factors influencing on stock market performances in the long run while solving " Stock price-GDP puzzle" in the Sri Lankan market. The results show that money supply and inflation are positively related with stock market performances and exchange rate, GDP and interest rate are negatively related to the stock market performances. "Stock price- GDP Puzzle" was solved by adding the balance of trade in the model where it finds positive association between GDP and stock price indicator. This study contributes to the literature on the relationship between stock market performances and macro economic factors while solving "Stock Price-GDP Puzzle". Keywords: All Share Price Index(ASPI), Market capitalization, Macro Economic factors, Sri Lanka JEL Classifications: E44, F36, G00, O16